2013
DOI: 10.4000/abe.376
|View full text |Cite
|
Sign up to set email alerts
|

Love and loathing in Cape Town

Abstract: Today, the platonic forms of the modernist, Corbusian-inspired Werdmuller Centre, by South African architect and urban designer Roelof Uytenbogaardt, stand against a background of decay in a neglected corner of Claremont, Cape Town. Controversial ever since its construction in the 1970s, the building is again the vortex of a dispute. It has been subject to a process of consideration for “heritage worthiness”, drawing public attention in the post-colonial, post-apartheid present to the contemporary significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Yet the irony of what we found in the contemporary landscape was only a ruin, in place of the romantic building (Figure 6). The trajectory of the passage of the building into ruin is paralleled by the claims and calls for Uytenbogaardt's work to be celebrated in the category of modern heritage (Murray, 2013b).…”
Section: Photobooking Steinkopfmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the irony of what we found in the contemporary landscape was only a ruin, in place of the romantic building (Figure 6). The trajectory of the passage of the building into ruin is paralleled by the claims and calls for Uytenbogaardt's work to be celebrated in the category of modern heritage (Murray, 2013b).…”
Section: Photobooking Steinkopfmentioning
confidence: 99%
“…Since 2009 we have been collecting and constructing our own research archive, and we have visited, photographed, and documented a large percentage of Uytenbogaardt's public buildings, projects, and sites across South Africa. These include the Crown Mines Project (Murray, 2018), the Welkom South Nederlandse Gereformeerde church, the University of Cape Town's Sports Centre, the Werdmuller Centre (Murray, 2013b), the Salt River Community Centre, the Bonwitt Factory (now the Hilton Double Tree Hotel), the Garden of Remembrance (Simonstown) and the Steinkopf Community Centre. The Steinkopf Community Centre is the topic of this paper Learning from Steinkopf to reference Venturi and Scott Brown's contribution to thinking about architecture and heritage differently (Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Letters have been very crucial in uncovering women’s histories as women took to this medium with some enthusiasm from the 18th century onwards (Earle, 2016). In South African historiography there is an abundance of published correspondence from settler women, and the wives of colonial officials who sought to bridge the distance between home and colony (Erlank, 1995; Fairbridge, 1927; Gordon, 1970; Harington, 1997; Murray, 1953; Warner, 1991). In 1987 Shula Marks, who published the correspondence of ‘three exceptional women’—Lily Moya, Mabel Palmer and Sibusiswe Makhanya—observed that women were ‘hidden from history’ with black women ‘doubly hidden’ (Marks, 1987, p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Much of our collaborative work has furthered our dialogue around the buildings of South African architect Roelof Uytenbogaardt (who followed Scott Brown and others from South Africa to study at the University of Pennsylvania under Louis Kahn from the 1960s) (Chipkin, 2008). In visiting key sites of Uytenbogaardt's architecture in South Africa we have sought to think about how apartheid's modernities have rendered these works and places complicated and tainted in the postapartheid (Murray, 2010). In documenting and photographing these key sites the idea of the road trip has become central to our methodology in making our own work.…”
mentioning
confidence: 99%